Graft-to-recipient weight ratio exerts nonlinear effects on prognosis by interacting with donor liver macrosteatosis - Liu, Zhengtao; Lyu, Jingting; Li, Xiang; Yu, Lu; Que, Shuping; Xu, Jun; Geng, Lei; Zheng, Shusen (Frontiers in Surgery, 2023)
Aim: To investigate the interactions between graft-to-recipient weight ratio (GWRWR) and other risk factors on inferior allograft outcomes. Methods: 362 patients who received liver transplantation (LT) were enrolled. Indicators were collected, including graft/recipient weight and other prognostic factors. Comparisons of indicators and survival analysis were performed in groups categorized by GWRWR. Interactions of large-for-size grafts (LFSGs) with graft macrosteatosis (MaS) were evaluated by relative excess risk due to interaction(RERI) and attributable proportion (AP). Cytoscape visualized the role of LFSGs in risk profile for poor prognosis. Results: Based on GWRWR, LT cases can be categorized into three subgroups with standard (1-2.5%), optimal (2.5-3.0%) and inferior prognosis (>3.0%). Survival analysis confirmed clear separations in cases categorized by the above-defined limits on GWRWR (P<0.05). LFSGs caused inferior prognosis by positive interactions with MaS severity. Conclusion: GWRWR exerted non-linear effects on prognosis in deceased donor LT cases. LFSGs (GWRWR>3.0%) caused inferior outcomes, while grafts sized within (2.5-3.0%) had optimal post-transplant prognosis. MaS increased the risk of poor prognosis by positive synergistic effects with LFSGs.